The first church of Matanzas: controversial aspects of its history (Islas, 2021)
The first church of Matanzas, located on the north coast of Cuba, was founded along with the city in October 1693. The founding of the city and church were part of a military plan which sought to establish a permanent settlement in one of Cuba’s most important bay ports and extend ecclesiastic practices to the island’s hinterland. Although the history of Matanzas' first church is discussed in most of the traditional historiography, several errors have been repeated without revision or correction since. Here we provide a detailed historiographic and archaeologic analysis which, along with novel evidence, reveals new data regarding the evolution and function of the city’s primitive church. Nevertheless, several incongruences call for further investigation. Among these are the cause and timing of the first temple’s disappearance, remodeling or reconstruction, and later translocation to a new location.
Keywords: first church; foundation; Matanzas city; urbanism; Catholicism; Cuba